2017
DOI: 10.7860/jcdr/2017/23960.9396
|View full text |Cite
|
Sign up to set email alerts
|

Study of Nitrosative Stress in ‘Pregnancy Induced Hypertension’

Abstract: Introduction: Hypertension is the most common medical problem encountered during pregnancy. Pregnancy Induced Hypertension (PIH) is also called a disease of maternal endo thelium. Nitricoxide being a potent vasodilator released by endothelial cells, its role has been implicated in PIH. Aim:To study the role of reactive nitrogen species in PIH. Materials and Methods:One hundred and twenty samples were selected for the study. Of these, 60 patients had PIH (case) and the rest without PIH (control). Estimation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…With those pathological changes, a series of cytotoxic factors will be released into the maternal body and lead to increased intravascular permeability. Finally, PIH patients will show prethrombotic symptoms and excessive coagulation substances will be released, which in turn lead to elevated blood hs-CRP level ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…With those pathological changes, a series of cytotoxic factors will be released into the maternal body and lead to increased intravascular permeability. Finally, PIH patients will show prethrombotic symptoms and excessive coagulation substances will be released, which in turn lead to elevated blood hs-CRP level ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few of the related studies were reported by Acharya et al [11], Dixit et al [12], Kolli et al [13]. Gaikwad et al reported about pregnancy induced hypertension [14]. Inamdar et al reported about hypertriglyceridemia and hypercholesterolemia in a case with gestational diabetes mellitus [15].…”
Section: Discussionmentioning
confidence: 99%
“…Vision 2015 of MCI emphasizes on 'Competency-based learning' and insists for assessment of newer learning experiences, competencies, along with certification of essential skills 11 . Due attention is needed on patient specific systemic conditions like diabetes [12][13][14][15][16][17] , hypertension [18][19][20][21][22][23][24][25][26] , respiratory and renal disorders [27][28][29][30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%